2020
DOI: 10.1071/an17082
|View full text |Cite
|
Sign up to set email alerts
|

Production and quality of the silage of sorghum intercropped with Paiaguas palisadegrass in different forage systems and at different maturity stages

Abstract: As part of the search for sustainability in production systems, systems of annual crops intercropped with tropical forage plants have recently been used for silage production. Therefore, in the present study we aimed to evaluate the dry matter yield, fermentative parameters and nutritional value of the silage of sorghum intercropped with Paiaguas palisadegrass in different forage systems and maturity stages in a crop-livestock integration system. The experiment was conducted at the Goiano Federal Institute (In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 29 publications
4
26
1
Order By: Relevance
“…This can be explained by the higher crude protein content and lower fibre fractions of the forages, which contributed to the better digestibility of the silage. The IVDMD values obtained here are consistent with the values found in other studies (Skonieski et al, 2010;Cruvinel et al, 2017;S. S. Oliveira et al, 2020;Taveira et al, 2020).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This can be explained by the higher crude protein content and lower fibre fractions of the forages, which contributed to the better digestibility of the silage. The IVDMD values obtained here are consistent with the values found in other studies (Skonieski et al, 2010;Cruvinel et al, 2017;S. S. Oliveira et al, 2020;Taveira et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…The TDN content of the silages was not influenced by the addition level, forage type or their interaction, and its average value was 600.18 g kg -1 DM. These values were above those found by S. S. Oliveira et al (2020) for Paiaguas palisadegrass silage (531.5 g kg -1 DM) and below those found for grain sorghum silage (663.5 g kg -1 DM). The difference in the contents above is due to the sorghum hybrid; sweet sorghum has a lower number of grains in the panicle than grain sorghum and provides less energy as a result (Taveira et al, 2020).…”
Section: Paiaguas Palisadegrass and Ipypora Grass Are Very Productive Forages That Havecontrasting
confidence: 55%
See 1 more Smart Citation
“…However, the lowest production of DM was obtained by Paiaguas palisadegrass monocropped forage system, demonstrating that the intercropping has contributed for the rise of DM production in 110.6; 127.9 and 48.9%, in the rows, inter-rows and oversown intercropped, respectively. Several studies have evidenced the benefits of producing silages from intercropping systems (Ribeiro et al, 2017;Cruvinel et al, 2017;Souza et al, 2019;Oliveira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…BRS Paiaguas is a great option, the plant attends all the requirements needed in different systems of production, encompassing different technological levels (Costa et al, 2016). Besides that, the forage has been used for the production of silage in integrated systems, allowing great results (Santos et al, 2016;Costa et al, 2018;Souza et al, 2019;Oliveira et al, 2020). Cruvinel et al (2017) reported that the silage of additive sunflowers with tropical forages are able to bring great benefits to the quality of the silage, for example, decrease in the content of ethereal extract, in the fibers of acid detergents, lignin, in addition to the production of silage in the off season, with good quality and with sufficient amount for nutritional maintenance of ruminants.…”
Section: Introductionmentioning
confidence: 99%